2015
DOI: 10.3390/met5021045
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Particles during Macro- and Micro-Weldings Procedures in Industrial Indoor Environments and Health Implications for Welding Operators

Abstract: Abstract:One of the emerging risks in the engineering and electronic industries is the exposure of workers to ultrafine particles during (micro-)welding operations, i.e., processes used for joining two metal parts heated locally, which constitute the base metal, with or without addition of another metal which is the filler metal, melted between the edges to be joined. The process is accompanied by formation of metallic fumes arising from the molten metal as well as by the emission of metal fumes of variable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The methodology of particle dose calculation has been thoroughly described in previous papers [30,31,32,33,34,35,36], where the particle deposition in the human respiratory system was evaluated using the Multiple-Path Particle Dosimetry model (MPPD v2.1, ARA 2009, ARA, Arlington, VA, USA). This model calculates, in the respiratory tract, the deposition and clearance of mono- and poly-disperse aerosols in the range from ultrafine to coarse particles in the respiratory tract [37,38].…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of particle dose calculation has been thoroughly described in previous papers [30,31,32,33,34,35,36], where the particle deposition in the human respiratory system was evaluated using the Multiple-Path Particle Dosimetry model (MPPD v2.1, ARA 2009, ARA, Arlington, VA, USA). This model calculates, in the respiratory tract, the deposition and clearance of mono- and poly-disperse aerosols in the range from ultrafine to coarse particles in the respiratory tract [37,38].…”
Section: Methodsmentioning
confidence: 99%
“…McGarry et al (50) laser printers operation, extruder process, clay process, MWCNT decanting, SWCNT synthesis Gomes et al (51) , Avino et al (52) welding processes…”
Section: Resultsmentioning
confidence: 99%
“…Järvela et al found particle number concentrations in ferrochromium and stainless steel production from 5.8 × 10 4 particles/cm 3 to 6.62 × 10 5 particles/cm 3 in the production areas [ 14 ]. Welding is another example of a relevant work-task where exposure is studied [ 29 , 30 , 50 ] the duration of welding tasks is however, shorter in time and thus les comparable in this context. Both Evans et al, (2017) and Järvela et al, (2016) report their results as total concentration measured by SMPS instruments, which could be one explanation for higher concentrations in these studies [ 14 , 15 ], another explanation could be real differences between the industries.…”
Section: Discussionmentioning
confidence: 99%